2021
DOI: 10.3390/agronomy11061165
|View full text |Cite
|
Sign up to set email alerts
|

Productivity of Paddies as Influenced by Varied Rates of Recommended Nutrients in Conjunction with Biofertilizers in Local Landraces

Abstract: This research work explores the productive performance of local paddy landraces under different fertility levels as well as the role of microbial inoculants in improving the yields of paddy landraces and reducing nutrient additions by increasing nutrient use efficiency under changing climatic scenarios in coastal areas. The landrace Padmarekha recorded taller plants, more tillers per hill, higher total dry matter accumulation other than grain and straw yields besides better uptake of N, P2O5, K2O, S and Zn. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 36 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…This shows that the rice plant received nitrogen from organic sources gradually and that it could be available at lower doses than synthetic fertilizer, which is commonly available. These findings confirm ( Goutami et al, 2018 ; Jana, Mondal & Mallick, 2020 ; Nataraja et al, 2021 ). Adequate dietary sources promoted post-anthesis dry matter accumulation (DMA) in grain ( Iqbal et al, 2020 ; Wu et al, 2021 ).…”
Section: Resultssupporting
confidence: 80%
“…This shows that the rice plant received nitrogen from organic sources gradually and that it could be available at lower doses than synthetic fertilizer, which is commonly available. These findings confirm ( Goutami et al, 2018 ; Jana, Mondal & Mallick, 2020 ; Nataraja et al, 2021 ). Adequate dietary sources promoted post-anthesis dry matter accumulation (DMA) in grain ( Iqbal et al, 2020 ; Wu et al, 2021 ).…”
Section: Resultssupporting
confidence: 80%
“…Azospirillum , Bacillus megatherium var. Phosphoticum, Frateuria quaratia , Thiobacillus thiooxidans and mycorrhiza combined with 100% dose of recommended fertilizers treatment significantly improved grain yield, nutrient content and biomass of the rice landrace Padmarekha (Nataraja et al, 2021).…”
Section: Improvement Of Soil Qualitymentioning
confidence: 99%
“…Comparable increases in organic carbon, available N, P and K through addition of organic materials was also reported (Carpenter-Boggs 2000 and Melero et al 2008). Superior soil fertility status on organic farms compared to soils fertilized with chemical fertilizers was also reported by Mader et al 2002and Nataraja et al 2021. Rasool et al (2007 observed that the average mean weight diameter (MW D), total porosity and water holding capacity (WHC) were highest in FYM treated plots both in rice (0.237 mm) and wheat (0.249 mm).…”
Section: Soil Quality Parametersmentioning
confidence: 67%